Acoustic micro‐beam vortex generator for flow actuation inside droplets - Diego Sánchez‐Saldaña; Maria Fernandino; Carlos A. Dorao (Droplet, 2024)
Abstract Controlling acoustic streaming inside a droplet has excellent potential for enabling fluid and particle operations such as mixing, separation, and aggregation in various applications. Most concepts for generating surface acoustic waves are based on the placement of an interdigitated transducer at the side of a droplet, thus externally acting on the droplet. In this case, the flow structure inside the droplet is controlled by the relatively large scale of the interdigitated transducer compared to the droplet, thus limiting the local control of the flow. One possibility to overcome this drawback is to reduce the size of the actuator such that a highly focused ultrasound transducer can induce localized acoustic streaming in space. Here, we introduce a micro‐spiral interdigitated transducer smaller than a droplet size that can generate micro‐size vortices inside the droplet. This step enables a new way of controlling the flow inside the droplet, facilitating mixing, separation, aggregation, and patterning of particles. We study the characteristics of the acoustic streaming and the potential application of the flow for the separation and patterning of particles. The simplicity of the concept provides in‐droplet particle manipulation toolsets for many applications such as biosensing, microbiology, and point‐of‐care devices.